Hepatic glucokinase regulatory protein and carbohydrate response element binding protein attenuation reduce de novo lipogenesis but do not mitigate intrahepatic triglyceride accumulation in Aldob deficiency - Amée M. Buziau; Maaike H. Oosterveer; Kristiaan Wouters; Trijnie Bos; Dean R. Tolan; Loranne Agius; Brian E. Ford; David Cassiman; Coen D.A. Stehouwer; Casper G. Schalkwijk; Martijn C.G.J. Brouwers (Elsevier, 2024)
Objective: Stable isotope studies have shown that hepatic de novo lipogenesis (DNL) plays an important role in the pathogenesis of intrahepatic lipid (IHL) deposition. Furthermore, previous research has demonstrated that fructose 1-phosphate (F1P) not only serves as a substrate for DNL, but also acts as a signalling metabolite that stimulates DNL from glucose. The aim of this study was to elucidate the mediators of F1P-stimulated DNL, with special focus on two key regulators of intrahepatic glucose metabolism, i.e., glucokinase regulatory protein (GKRP) and carbohydrate response element binding protein (ChREBP). Methods: Aldolase B deficient mice (Aldob−/−), characterized by hepatocellular F1P accumulation, enhanced DNL, and hepatic steatosis, were either crossed with GKRP deficient mice (Gckr−/−) or treated with short hairpin RNAs directed against hepatic ChREBP. Results: Aldob−/− mice showed higher rates of de novo palmitate synthesis from glucose when compared to wildtype mice (p < 0.001). Gckr knockout reduced de novo palmitate synthesis in Aldob−/− mice (p = 0.017), without affecting the hepatic mRNA expression of enzymes involved in DNL. In contrast, hepatic ChREBP knockdown normalized the hepatic mRNA expression levels of enzymes involved in DNL and reduced fractional DNL in Aldob−/− mice (p < 0.05). Of interest, despite downregulation of DNL in response to Gckr and ChREBP attenuation, no reduction in intrahepatic triglyceride levels was observed. Conclusions: Both GKRP and ChREBP mediate F1P-stimulated DNL in aldolase B deficient mice. Further studies are needed to unravel the role of GKRP and hepatic ChREBP in regulating IHL accumulation in aldolase B deficiency.